Pyomyositis in a Patient with IgA Nephropathy and Kidney Transplant - M. Xipell; P. Ventura-Aguiar; I. Revuelta; M. Bodro; F. Diekmann (Case Reports in Transplantation)
Infections are among the most common complications transplant physicians face when dealing with solid organ transplant recipients. We present a case of pyomyositis caused by Staphylococcus aureus in a patient with IgA nephropathy and a kidney transplant, under treatment with mTOR inhibitors and prednisone. This entity is a rare intramuscular infection, given the resistance of healthy muscle to colonization. We review the most frequent agents, the diagnostic algorithm, and therapeutic alternatives. We also comment on the role of mTOR inhibitors in this case as possible predisposing factor for the infection.